the disinterested school: poetry as a path to emancipation and transformation in public schools - ferreira, maria onete lopes (childhood & philosophy, 2024)
This article offers a reflection that arose as a result of an experience with literature, poetry, and philosophy in school, specifically in early-grade primary school classes, starting in 2011. This experience led to a research, teaching, and professional development project that is now in progress in public schools. The project’s critical-methodological basis is a critique of schooling that is directed toward utilitarian ends. This approach has remained dominant, despite innumerable changes to the curriculum over the years. It is unfortunate that the concern that motivates curricular changes tends to be based on factors such as poor learning outcomes as reflected in students who fail grades, skip school, or drop out, without considering how these trends might be the product of their experience of school itself. In light of this, this article advocates for the type of schooling that Gramsci described as disinterested and proposes literature and poetry as tools to advance the transformative pedagogical project. A study of the scholarship on poetry, along with the insights gained from the experience in question, enables us to develop a conception of revolutionary schooling in the Gramscian and emancipatory sense as proposed by Paulo Freire. The article therefore proposes connections to happiness, which combines the objective of the disinterested school with Epicurean philosophy. Poetry is understood as a path through which to envisage the valorization of the ludic, which is among the most important aspects of childhood learning.